Effects of dietary propolis and vitamin E on growth performance and antioxidant status in juvenile rainbow trout (Oncorhynchus mykiss) under different flow rate - Kelestemur, Guluzar Tuna; Seven, Ismail (Wiley, 2013)
The present study investigated the effects of propolis and vitamin E supplementation in diets of juvenile rainbow trout subjected to two different flow rates (0.9 and 2.1Lmin-1) on growth performance, and vitamin A, C and E concentrations in tissues as well as malondialdehyde (MDA) levels. Juvenile rainbow trout were fed with diets containing 10 and 30gpropoliskg-1, 60mgkg-1 vitamin E (Rovimix E-50 adsorbate; min.%50dl--tokopherly acetate) and without supplemented basal diet for 12weeks. Weight gain (WG) in the C group was significantly lower (P<0.05) than P10, P30 and E60 groups at both flow rate treatments. At 2.1Lmin-1, specific growth rate (SGR) in the C group was significantly lower (P<0.05) than other groups, but at 0.9Lmin-1, SGR of fish did not differ among the diets groups (0.05). Survival rate (SUR) was higher in propolis and vitamin E supplemented diet groups (P<0.05) than control diet group at 0.9Lmin-1. Fish fed on diet E60 had higher (P<0.05) tissue vitamin E concentration than fishes fed on other diets groups. Vitamin C concentration in rainbow trout tissues was significantly affected by the 30g propolis supplemented diet group (P<0.05), followed by the 10g propolis supplemented diet group (P<0.05). MDA level of E60 group was found significantly decreased instead of different than other groups (P<0.05). The results of Student's t-test revealed that WG, SGR, SUR values, vitamin (A, C, E) concentrations and MDA levels of tissues were negatively affected by 0.9Lmin-1flow rate treatment in juvenile rainbow trout.
Keywords: rainbow trout; diet; vitamin E; propolis; hypoxic stress; tissue